Penerapan Model Think, Pair, and Share Berbasis Alat Peraga untuk Meningkatkan Kemampuan Berpikir Kritis Siswa - Sintikhe Syela Adu; Wiputra Cendana (Madako Elementary School, 2022)
The ability to think critically is the potential of humans to maximize the learning process. Abstract learning is important for students to understand by maximizing critical thinking patterns. It is the task of the teacher as a facilitator to design a learning model that is in accordance with the characteristics of students. This research was conducted at a school in Lampung and aims to describe the application of the Think, Pair, and Share model based on teaching aids to improve students' critical thinking skills. There were 24 students studied in this research. The research method used is the descriptive-qualitative method. A teacher has a role and responsibility in facilitating students' understanding of basic concepts through the development of critical thinking patterns. The results of this research indicate that the application of the TPS model based on teaching aids can improve students' critical thinking skills. The suggestion from the author is that the teacher can modify this teaching aid with other technologies, and the application of the TPS model can be carried out in more than two learning sessions for maximum results.